Methodology to Identify High-Priority Interventions for Sustainable Urban Regeneration in Informal Settlements in Lmics: A Case Study in Lima - Acevedo De los Ríos, Alejandra (2022)
Urban areas in low-and middle-income countries (LMICs) are rapidly expanding, leading to a significant proportion of the population living in informal settlements (IS). These settlements are characterized by their socioeconomic disadvantage and being generally located in vulnerable areas along with disconnection from basic services. Urban regeneration projects in IS have increased, however, the absence of a defined method for prioritizing the interventions to be performed has produced a mismatch between the implemented interventions and the local needs. Instead, these interventions tend to respond to preconceived agendas, which, in turn, leads to the creation of unsustainable projects. In this regard, this study proposes a three-phase methodology to identify priority interventions in terms of sustainable urban regeneration (SUR) in IS. In the first phase, a diagnostic matrix composed of 4 dimensions, 18 variables, and 61 indicators is built based on a literature review of SUR. In the second phase, an interactive, publicly accessible web instrument is developed to visualize the indicator data for Metropolitan Lima. In the last phase, the instrument is tested, which results in a district-level diagnosis. The proposed methodological approach facilitates objective, rigorous quantitative analysis for local governments to optimize financial resource utilization and facilitate decision-making.